2019
DOI: 10.15244/pjoes/94841
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Natural Palygorskite and its Modified Form on Alleviation of Heavy Metals Toxicity to Tomato Grown in Soil Contaminated with Cd, Pb and Zn

Abstract: A field experiment was conducted to investigate differential effects of natural palygorskite (PAL) and its modified form (KH550-PAL) on the alleviation of heavy metals toxicity to tomatos grown in contaminated soil with Cd, Pb and Zn. Compared to heavy metal-contaminated soil without amendment, the application of natural palygorskite (PAL) or its modified form (KH550-PAL) significantly alleviated heavy metal toxicity to tomato. In addition, foliar malondialdehyde (MDA), hydrogen peroxide (H 2 O 2) and superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…It can damage the membrane properties, which is estimated from the increased MDA contents. Similar findings have been concluded in Arabdopsis thaliana exposed to As stress [61]. Malondialdehyde (MDA) is an indicator of occurrence of lipid peroxidation due to oxidative damage, which is detected in spinach leaves when grown in presence of As [62].…”
Section: Resultssupporting
confidence: 79%
“…It can damage the membrane properties, which is estimated from the increased MDA contents. Similar findings have been concluded in Arabdopsis thaliana exposed to As stress [61]. Malondialdehyde (MDA) is an indicator of occurrence of lipid peroxidation due to oxidative damage, which is detected in spinach leaves when grown in presence of As [62].…”
Section: Resultssupporting
confidence: 79%
“…As two primary antioxidative enzyme, previous studies revealed that SOD and POD play a relevant role in treatment of heavy metal enhances ROS formation [44,45]. SOD can eliminate O 2-, decrease peroxidation of membrane lipids and maintain cell membrane stability, and POD participate in the decomposition of H 2 O 2 [25,46]. In the present study and other studies showed that the activities of POD significantly increased and correlated with heavy metal stress, suggesting that plants adjusted their POD activity to protect membrane stability from heavy metal-induced oxidative damage [37,47] (Fig.…”
Section: Discussionmentioning
confidence: 99%